DEVELOPMENT OF INFORMATIONAL AWARENESS AMONG STUDENTS UNDER THE CONDITIONS OF DIGITAL EDUCATION IMPLEMENTATION IN YAKUTIA - Afanasieva Barakhsanova, Elizaveta; Petrovich Olesov, Nikolai; Vitalievna Popova, Liudmila; Iliinichna Danilova, Anna; Semyonovich Diachkovskyi, Nikolai (Gênero & Direito, 2020)
This study was aimed at determining the effectiveness and potential of pedagogical education to develop informational awareness among students under the conditions of educational digitalization in Yakutia, also known as the Republic of Sakha. The problem was investigated primarily through an analysis of the theoretical viewpoints put forward by foreign and Russian researchers on issues regarding updates to education in the informational education space. The loss of moral and value orientations in society and the upbringing amid this backdrop of an entire generation of youth, who are currently becoming educators of a new rising generation, cause societal apprehension and highlight the need to find a solution. Correspondingly, this research probed into the effectiveness with which the following requirement is implemented in the chosen context: capitalizing on the potential of ethnic pedagogy in advancing the evolution of students’ ability to discern and adequately assess the effects of informational environments on youth development. A pedagogical experiment was conducted at the M. K. Ammosov North-Eastern Federal University to examine initial concepts regarding the fulfillment of ethnic pedagogy’s prospects for enhancing the educational value of academic activities in the university. More than 500 students from different colleges and faculties, as well as lecturers who are involved in extracurricular activities, took part in the experiment. The study treated updates in service of the potential of ethnic pedagogy to mold the young generation under the digitalization of the educational process in a regional university as scientific results. The practical significance of the study was established in consideration of the characteristics of media influence, Internet addiction, and psychophysiological stress and in accordance with the requirements of the newly instituted Federal State Educational Standard 3++ (FSES 3++). The obtained methodological and technological data on the development of informational awareness among students can be used in explorations into other areas of education